Preparation method of catalyst for preparing sustainable aviation fuel through CO2 hydrogenation

By introducing carbon sources such as carbon nanotubes and Fe-based active sites into the catalyst, and adding alkali metal promoters, the problems of low conversion rate and selectivity in the preparation of aviation fuel by CO2 hydrogenation were solved, and efficient and stable catalyst performance was achieved.

CN120900654APending Publication Date: 2025-11-07SHANGHAI HUA FENGHE BIOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511286266.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing technologies for producing aviation fuel by hydrogenating CO2 suffer from problems such as low CO2 conversion rate, low selectivity of aviation fuel, and poor catalyst stability.

Method used

A catalyst was prepared by coprecipitation using carbon nanotubes, activated carbon, glucose or polyol as carbon sources, combined with FeMn, FeZn or FeGa as active sites, and alkali metal Li, Na or K as promoters, to promote the highly selective hydrogenation of CO2 to generate aviation fuel.

Benefits of technology

The selectivity and catalyst stability of CO2 hydrogenation for aviation fuel production have been improved, achieving high conversion rate and high selectivity in aviation fuel production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120900654A_ABST
    Figure CN120900654A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a catalyst for hydrogenation of CO2 to sustainable aviation fuel (SAF). The catalyst stabilizes FeCx active sites through carbon species, and comprises the following steps: (a) carbon nanotubes, activated carbon, glucose or polyol are used as a carbon source, (b) FeMn, FeZn or FeGa are used as active sites, and (c) alkali metal Li, Na or K is used as an auxiliary agent to promote adsorption of CO2. According to the catalyst, active metal is deposited on carbon species through a coprecipitation method, and the catalyst prepared through the synthesis method not only can weaken oxidation of H2O on FeCx active sites, but also is beneficial to increase of carbon chains to promote CO2 hydrogenation to generate aviation fuel with high selectivity. The invention discloses a preparation method of a high-stability Fe-based catalyst for hydrogenation of CO2 to SAF.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of green fuel, and particularly relates to a method for preparing sustainable aviation fuel by CO2 hydrogenation and a corresponding catalyst preparation. BACKGROUND

[0002] The current production method of aviation fuel is mainly obtained by distillation of petrochemical crude oil, which seriously depends on petroleum resources. With the continuous growth of global energy demand and the increasing awareness of environmental protection, finding clean and efficient alternative energy has become an important issue in the energy field. The conversion of CO2 into liquid fuels or high-value chemicals has attracted great interest from researchers. However, the challenge of this process is that CO2 is a thermodynamically stable and chemically inert molecule.

[0003] The species synthesized by CO2 hydrogenation reaction will tend to generate short-chain compounds (CH4, methanol, formic acid, C2-C4 low-carbon olefins, etc.) rather than ideal long-chain hydrocarbons. In recent years, through the construction of bifunctional or tandem catalysts, some breakthroughs have been made in the direct synthesis of gasoline (C5-C9 short-chain hydrocarbons) from CO2 hydrogenation, but there are few reports on the selective synthesis of aviation kerosene. Based on this, if CO2 can be converted into sustainable aviation kerosene (SAF) in one step, it not only can reduce our country's dependence on petroleum resources, but also can make up for the energy shortage problem caused by the energy structure characteristics of "rich coal, poor oil, and little gas" in our country.

[0004] The main method of CO2 hydrogenation direct synthesis of liquid fuel involves CO intermediates formed by the cascade of reverse water-gas shift (RWGS) and Fischer-Tropsch synthesis (FTS) reactions. However, methanation of CO2 or CO will also occur, which will reduce the hydrocarbon selectivity of the process. In the case of following the FTS mechanism, the aviation fuel fraction (C8-C 16 ) selectivity will not exceed 41% (determined by ASF distribution). Therefore, how to break through the ASF distribution limit to improve the selectivity of aviation fuel and promote C-C coupling reaction to increase the carbon number is one of the extremely challenging goals.

[0005] Yao et al. [Nat. Commun, 2020, 11 (1): 6395] reported a bifunctional Fe-Mn-K catalyst synthesized by an organic combustion method, which converted CO2 into aviation kerosene through the tandem of RWGS (Fe3O4) and FTS (χ-Fe5C2) reactions. Under the reaction conditions of 1 MPa, 300℃, 2400 mL / g cat ·h and H / C = 3, the CO2 conversion rate reached 38.2%, and the C8-C 16The selectivity is 47.8%, the yield is 17.2%, and the selectivity of CO and CH4 is low (5.6% and 10.4%). Zhang et al. [The Innovation, 2021, 2(4)] reported a Na-modified CoFe alloy catalyst prepared from CoFe hydrotalcite as a precursor, which has a high aviation fuel selectivity (63.5%) under the reaction conditions of 240℃, 5500mL / g cat·h, H / C=3 and 3MPa, wherein the CO2 conversion is 10.2%, and the total selectivity of CO and CH4 by-products is less than 22%; this is mainly due to the promotion of C-C coupling reaction and the inhibition of RWGS reaction by Na promoter and CoFe alloy structure. However, the low CO2 conversion in this technology leads to low overall efficiency. In summary, the current reported CO2 hydrogenation to aviation kerosene generally has low CO2 conversion, low aviation kerosene selectivity, and poor catalyst stability. The present specification will provide a new method for preparing a high-efficiency and high-stability Fe-based catalyst for directly hydrogenating CO2 to produce sustainable aviation fuel. SUMMARY

[0006] In view of the problems existing in the prior art, the purpose of the present application is to provide a catalyst preparation method for high-selectivity hydrogenation of CO2 to aviation fuel. It comprises: (a) using carbon nanotubes, activated carbon, glucose or polyols as carbon sources, (b) FeMn, FeZn or FeGa as active sites, (c) using alkali metals Li, Na or K as promoters to promote CO2 adsorption, and depositing active metals on carbon species by co-precipitation method. The catalyst prepared by this synthesis method can not only reduce the oxidation of FeC x active sites by H2O, but also facilitate carbon chain growth, promoting high-selectivity hydrogenation of CO2 to aviation fuel.

[0007] The technical solution adopted by the present application is: a high-stability Fe-based catalyst preparation method for preparing sustainable aviation kerosene by hydrogenation of CO2. Carbon species are introduced into Fe-based catalysts by co-precipitation method, and the hydrophobicity (which can avoid the oxidation of FeC x active sites by product H2O) and carbonation (which is conducive to the occurrence of C-C coupling) of carbon species are used to promote and improve the catalytic activity and selectivity of the catalyst in the process of preparing SAF by hydrogenation of CO2.

[0008] The following three factors are used to promote and improve the catalytic activity and selectivity of the catalyst in the process of preparing SAF by hydrogenation of CO2.

[0009] Firstly, carbon nanotubes, activated carbon, glucose or xylose are used as carbon sources to dope Fe-based catalysts in situ to stabilize FeC x active sites, avoid the change of active sites caused by the oxidation of product H2O, and thus improve the selectivity of aviation fuel.

[0010] Secondly, the introduction of carbon nanotubes, activated carbon, glucose or polyols as carbon species into the Fe-based catalyst is beneficial to the C-C coupling reaction and promotes the generation of high-carbon-chain aviation fuel components from CO2 hydrogenation.

[0011] Thirdly, the introduction of alkali metal elements into the Fe-based catalyst by vacuum impregnation can regulate the acidity and alkalinity of the catalyst to promote the adsorption and dissociation of CO2, achieving high conversion and high selective conversion of CO2 hydrogenation to aviation fuel.

[0012] The technical solutions for achieving the above-mentioned purposes of the present application can be summarized as follows:

[0013] 1. A method for preparing a high-stability catalyst for CO2 hydrogenation to sustainable aviation fuel (SAF), as claimed in claim 1, characterized in that carbon species are introduced into the Fe-based catalyst by the coprecipitation method, and the hydrophobicity (which can avoid the oxidation of the active site by product H2O) and carbonation (which is beneficial to the occurrence of C-C coupling) of the carbon species are used to selectively hydrogenate CO2 to aviation fuel. x

[0014] 2. A method for preparing a high-stability catalyst for CO2 hydrogenation to SAF, characterized in that the catalyst is prepared by the coprecipitation method, and the steps are as follows:

[0015] (1) Disperse a certain amount of one or more of carbon nanotubes, activated carbon, glucose or polyols as a carbon source in an aqueous solution of ethanol to obtain solution A;

[0016] (2) Simultaneously add active metal salt (FeMn, FeZn or FeGa) and 1 mol / L of alkaline precipitator dropwise into the above-mentioned solution A, keeping the solution pH = 8 during the dropwise addition process, until solution B is obtained after the dropwise addition is completed;

[0017] (3) Age solution B at room temperature, perform hydrothermal treatment, and finally filter, wash and dry to obtain powder C;

[0018] (4) Introduce a certain amount of alkali metal into powder C using ultrasonic-assisted impregnation, and then vacuum dry at 60°C for 12h. Finally, calcine in a N2 atmosphere to obtain a NaFeMn@C, NaFeZn@C or NaFeGa@C-based catalyst.

[0019] 3. The method according to any one of items 1-2, characterized in that step (1): one or more of carbon nanotubes, activated carbon, glucose or polyols are used as the carbon source, preferably glucose or xylose.

[0020] ​4. The method according to any one of items 1-3, characterized in that step (2): the amount of theoretical metal salt required is calculated according to the content of the metal oxide required and prepared into an aqueous solution, the metal salt being one or more of nitrate, chloride or sulfate; 1 mol / L Na2CO3, K2CO3 or Li2CO3 is prepared as a precipitant, and co-precipitation is carried out at 70-100°C, with pH = 8.0 maintained during the dropping process.

[0021] 5. The method according to any one of items 1-4, characterized in that step (3): the B solution is hydrothermally treated at 100-150°C for 12-15h, preferably at 130°C and for 15h.

[0022] 6. The method according to any one of items 1-5, characterized in that step (4): the alkali metal is one or more of Li, Na and K, with a content of 1wt%-5wt%, preferably Na, 1wt%. Finally, calcination is carried out at 400-700°C in a N2 atmosphere for 4-8h, preferably at 650°C and for 4h.

[0023] 7. The application of the Fe-based catalyst for the preparation of sustainable aviation fuel by the hydrogenation of CO2 according to any one of items 1-6, characterized in that FeC is obtained under carbonization conditions of pure H2 or (CO / H2) mixed gas at 350-400°C and 0.1-1MPa. x active species. Preferably, the carbonization conditions are pure H2 atmosphere, 400°C and 0.1MPa.

[0024] 8. The application of the Fe-based catalyst for the preparation of sustainable aviation fuel by the hydrogenation of CO2 according to any one of items 1-7, characterized in that the hydrogenation of CO2 to aviation fuel is carried out in a fixed bed reactor, characterized in that the reaction temperature is 300-400°C, with an optimal temperature of 350°C. The reaction mass space velocity is 5000-20000mL / gcat·h, with an optimal space velocity of 10000mL / gcat·h. The reaction pressure is 1-4MPa, with an optimal pressure of 3MPa. BRIEF DESCRIPTION OF DRAWINGS

[0025] The drawings described herein are used to provide further understanding of the present application, and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions serve to explain the present application, and do not constitute an improper limitation on the present application. In the drawings:

[0026] Figure 1 .CO2 hydrogenation reaction activity and stability test results for the preparation of aviation fuel DETAILED DESCRIPTION

[0027] In order to make the purposes, technical solutions and advantages of the present application clearer, the technical solutions of the present application will be described clearly and completely below in combination with specific embodiments of the present application and corresponding drawings. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.

[0028] Embodiment 1.

[0029] (1) Catalyst preparation

[0030] 1.0 g of carbon nanotubes was dispersed in 50 mL of an aqueous solution of ethanol (volume ratio of 1 / 1) as a carbon source, and ultrasonic dispersion was performed for 30 min to obtain solution A; 200 mL of a 0.27 mol / L FeMn (molar ratio: Fe / Mn = 7 / 3) nitrate solution and 1 mol / L Na2CO3 basic precipitator were simultaneously added dropwise into the above solution A, and the pH of the solution was kept at 8 during the whole dropwise addition process, until solution B was obtained after the dropwise addition was completed; the B solution was aged at room temperature for 48 h, and then filtered, washed and dried at 60℃ to obtain powder C; then 1 wt% of alkali metal Na was introduced into the powder C by an ultrasonic-assisted impregnation method, and vacuum drying was performed at 60℃ for 12 h. Finally, the NaFeMn@C catalyst was prepared by calcining at 650℃ (2℃ / min) for 4 h in a N2 atmosphere.

[0031] (2) Catalyst performance test

[0032] The test of preparing SAF from CO2 hydrogenation was performed in a fixed bed reactor. 1 g of NaFeMn@C catalyst with a particle size of 40-60 mesh was mixed with 3 g of quartz sand of the same mesh size, and then loaded into the reactor. After reduction at 400℃ in a pure H2 atmosphere at normal pressure for 8 h, the temperature was cooled to below 100℃, then the raw material gas (20.0 mL / min CO2, 60.0 mL / min H2 and 3.3 mL / min N2) was switched in and the pressure was increased to 3 MPa, and then the temperature was increased to the reaction temperature of 350℃ at a rate of 2℃ / min to perform the CO2 hydrogenation reaction for preparing SAF, and the aviation fuel fraction was separated. The conversion rate and selectivity test results are shown in Table 1.

[0033] Embodiment 2.

[0034] (1) Catalyst preparation

[0035] 1.0 g activated carbon as carbon source was dispersed in 50 mL aqueous solution of ethanol (volume ratio: 1 / 1) and ultrasonic dispersion was performed for 30 min to obtain solution A; 200 mL of 0.27 mol / L FeZn (molar ratio: Fe / Zn = 7 / 3) nitrate solution and 1 mol / L Na2CO3 basic precipitant were simultaneously added dropwise into the above solution A, and the solution pH was kept at 8 during the whole process until the end of the dropwise addition to obtain solution B; the B solution was aged at room temperature for 48 h, and then filtered, washed and dried at 60°C to obtain powder C; then 1 wt% of alkali metal K was introduced into the powder C by ultrasonic assisted impregnation, and vacuum drying was performed at 60°C for 12 h. Finally, the KFeZn@C catalyst was prepared by calcination at 650°C (2°C / min) for 4 h in a N2 atmosphere.

[0036] (2) Catalyst performance test

[0037] The test of CO2 hydrogenation to prepare SAF was performed in a fixed bed reactor. 1 g of KFeZn@C catalyst with a particle size of 40-60 mesh was mixed with 3.0 g of quartz sand of the same mesh size, and then loaded into the reactor. After reduction at 400°C in a synthesis gas (H / C = 1 / 1) atmosphere at normal pressure for 8 h, the temperature was cooled to below 100°C, and then the raw material gas (20.0 mL / min CO2; 60.0 mL / min H2 and 3.3 mL / min N2) was switched in and the pressure was increased to 4 MPa. Subsequently, the temperature was increased to the reaction temperature of 350°C at a rate of 2°C / min to perform the CO2 hydrogenation to SAF reaction. The conversion and selectivity test results are shown in Table 1.

[0038] Example 3.

[0039] (1) Catalyst preparation

[0040] 1.0 g activated carbon as carbon source was dispersed in 50 mL aqueous solution of ethanol (volume ratio: 1 / 1) and ultrasonic dispersion was performed for 30 min to obtain solution A; 200 mL of 0.27 mol / L FeGa (molar ratio: Fe / Ga = 7 / 3) nitrate solution and 1 mol / L Na2CO3 basic precipitant were simultaneously added dropwise into the above solution A, and the solution pH was kept at 8 during the whole process until the end of the dropwise addition to obtain solution B; the B solution was aged at room temperature for 48 h, and then filtered, washed and dried at 60°C to obtain powder C; then 1 wt% of alkali metal Na was introduced into the powder C by ultrasonic assisted impregnation, and vacuum drying was performed at 60°C for 12 h. Finally, the NaFeGa@C catalyst was prepared by calcination at 650°C (2°C / min) for 4 h in a N2 atmosphere.

[0041] (2) Catalyst performance test

[0042] The test of CO2 hydrogenation to SAF was carried out in a fixed bed reactor. 1 g of NaFeGa@C catalyst with a particle size of 40-60 mesh was mixed with 3 g of quartz sand of the same mesh size, and then loaded into the reactor. After reduction at 400°C for 8 h in a (H / C = 1 / 1) atmosphere of 1 MPa of synthesis gas, the temperature was cooled to below 100°C, then the raw material gas (20.0 mL / min CO2; 60.0 mL / min H2 and 3.3 mL / min N2) was switched in and the pressure was increased to 3 MPa, and then the temperature was increased to the reaction temperature of 380°C at a rate of 2°C / min to carry out the CO2 hydrogenation to SAF reaction. The conversion and selectivity test results are shown in Table 1.

[0043] Example 4.

[0044] (1) Catalyst preparation

[0045] 1 g of carbon nanotubes was dispersed in 50 mL of an ethanol aqueous solution (volume ratio = 1 / 1) as a carbon source, and ultrasonic dispersion was carried out for 30 min to obtain solution A; 200 mL of a 0.27 mol / L FeZn (molar ratio: Fe / Zn = 7 / 3) nitrate solution and 1 mol / L Na2CO3 basic precipitant were added dropwise into the above solution A at the same time, and the pH of the solution was maintained at 8 during the whole dropwise addition process, until solution B was obtained after the dropwise addition was completed; solution B was aged at room temperature for 48 h, and then filtered, washed and dried at 60°C to obtain powder C; then 1.0 wt% of alkali metal Na was introduced into powder C by an ultrasonic-assisted impregnation method, and vacuum drying was carried out at 60°C for 12 h. Finally, the NaFeZn@C catalyst was prepared by calcination at 650°C (2°C / min) for 4 h in a N2 atmosphere.

[0046] (3) Catalyst performance test

[0047] The process of CO2 hydrogenation to SAF was carried out in a fixed bed reactor. 1 g of NaFeZn@C catalyst with a particle size of 40-60 mesh was mixed with 3 g of quartz sand of the same mesh size, and then loaded into the reactor. After reduction at 400°C for 8 h in a pure H2 atmosphere, the temperature was cooled to below 100°C, then the raw material gas (40.0 mL / min CO2; 120.0 mL / min H2 and 6.7 mL / min N2) was switched in and the pressure was increased to 3 MPa, and then the temperature was increased to the reaction temperature of 380°C at a rate of 2°C / min to carry out the CO2 hydrogenation to SAF reaction. The conversion and selectivity test results are shown in Table 1.

[0048] Example 5.

[0049] (1) Catalyst preparation

[0050] 2.5 g of glucose was dispersed in 50 mL of an aqueous solution of ethanol (volume ratio = 1 / 1) as a carbon source, and ultrasonic dispersion was performed for 30 min to obtain solution A; 200 mL of a 0.27 mol / L FeMn (molar ratio: Fe / Mn = 7 / 3) nitrate solution and 1 mol / L Na2CO3 basic precipitant were simultaneously added dropwise into the above solution A, and the pH of the solution was maintained at 8 during the entire dropwise addition process, until solution B was obtained after the dropwise addition was completed; the B solution was aged at room temperature for 48 h, and then transferred to a hydrothermal kettle with a polytetrafluoroethylene liner for static hydrothermal treatment at 130°C for 15 h, and then filtered, washed, and dried at 60°C to obtain powder C; then 1 wt% of alkali metal Na was introduced into the powder C by an ultrasonic-assisted impregnation method, and vacuum drying was performed at 60°C for 12 h. Finally, the NaFeMn@C catalyst was prepared by calcining at 650°C (2°C / min) for 4 h in a N2 atmosphere.

[0051] (3) Catalyst performance test

[0052] The process of preparing SAF by CO2 hydrogenation was carried out in a fixed bed reactor. 1 g of NaFeMn@C catalyst with a particle size of 40-60 mesh was mixed with 3 g of quartz sand of the same mesh size, and then loaded into the reactor. After reduction at 400°C in a pure H2 atmosphere for 8 h, the temperature was cooled to below 100°C, and then the raw material gas (40.0 mL / min CO2; 120.0 mL / min H2 and 6.7 mL / min N2) was switched in and the pressure was increased to 3 MPa. Subsequently, the temperature was increased to the reaction temperature of 350°C at a rate of 2°C / min to perform the CO2 hydrogenation to SAF reaction. The conversion and selectivity test results are shown in Table 1 and Figure 1 .

[0053] Example 6.

[0054] (1) Catalyst preparation

[0055] 1.0 g of carbon nanotubes was dispersed in 50 mL of an aqueous solution of ethanol (volume ratio = 1 / 1) as a carbon source, and ultrasonic dispersion was performed for 30 min to obtain solution A; 200 mL of a 0.27 mol / L FeMn (molar ratio: Fe / Mn = 7 / 3) nitrate solution and 1 mol / L Na2CO3 basic precipitant were simultaneously added dropwise into the above solution A, and the pH of the solution was maintained at 8 during the entire dropwise addition process, until solution B was obtained after the dropwise addition was completed; the B solution was aged at room temperature for 48 h, and then transferred to a hydrothermal kettle with a polytetrafluoroethylene liner for static hydrothermal treatment at 130°C for 15 h, and then filtered, washed, and dried at 60°C to obtain powder C; then 1 wt% of alkali metal Li was introduced into the powder C by an ultrasonic-assisted impregnation method, and vacuum drying was performed at 60°C for 12 h. Finally, the LiFeMn@C catalyst was prepared by calcining at 650°C (2°C / min) for 4 h in a N2 atmosphere.

[0056] (2) Catalyst performance test

[0057] The process of preparing SAF from CO2 hydrogenation was carried out in a fixed bed reactor. 1 g of LiFeMn@C catalyst with 40-60 mesh was mixed with 3 g of quartz sand with the same mesh number, and then loaded into the reactor. After reduction at 400℃ under pure H2 atmosphere for 8 h, it was cooled to below 100℃, then switched to the feed gas (20.0 mL / min CO2; 60.0 mL / min H2 and 3.3 mL / min N2) and pressurized to 4 MPa, and then heated to the reaction temperature 350℃ at 2℃ / min for CO2 hydrogenation to SAF reaction. The conversion and selectivity test results are shown in Table 1.

[0058] Table 1. Reaction performance results of CO2 hydrogenation to aviation fuel

[0059]

[0060] The above only describes the embodiments of the present application and is not intended to limit the present application. The present application can have various modifications and changes for those skilled in the art. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the right of the present application.

Claims

1. A method for preparing a catalyst for CO2 hydrogenation to sustainable aviation fuel (SAF): characterized in that, Carbon species are introduced into the Fe-based catalyst via co-precipitation, taking advantage of the hydrophobicity of the carbon species (which avoids the effect of product H2O on FeC). x The oxidation of active sites and carbonization (which facilitates the occurrence of CC coupling) allow for the highly selective hydrogenation of CO2 to produce aviation fuel.

2. A method for preparing a highly stable catalyst for CO2 hydrogenation to SAF as described in claim 1, characterized in that, The preparation steps using the co-precipitation method are as follows: (1) Disperse a certain amount of one or more of carbon nanotubes, activated carbon, glucose or polyol as a carbon source in an aqueous solution of ethanol to obtain solution A; (2) Add an active metal salt (FeMn, FeZn or FeGa) and a 1 mol / L alkaline precipitant dropwise to the above solution A, keeping the pH of the solution at 8 during the dropwise addition until solution B is obtained after the dropwise addition is completed; (3) The solution B was aged at room temperature, hydrothermally treated, and finally filtered, washed and dried to obtain powder C. (4) A certain amount of alkali metal was introduced into powder C by ultrasonic-assisted impregnation, and then vacuum dried at 60°C for 12 h. Finally, it was calcined in a N2 atmosphere to obtain NaFeMn@C, NaFeZn@C or NaFeGa@C based catalysts.

3. The method according to claim 2, characterized in that, Step (1): Use one or more of carbon nanotubes, activated carbon, glucose or polyols as carbon source, preferably glucose and xylose.

4. The method according to claim 2, characterized in that, Step (2): Calculate the theoretical amount of metal salt required according to the content of the required metal oxide and prepare an aqueous solution. The metal salt is one or more of nitrate, hydrochloride or sulfate. Then prepare 1 mol / L Na2CO3, K2CO3 or Li2CO3 as precipitant and co-precipitate at 70-100℃, keeping the pH = 8.0 during the dropwise addition.

5. The method according to claim 2, characterized in that, Step (3): Hydrothermally treat solution B at 100-150℃ for 12-15h, preferably 130℃ and 15h.

6. The method according to claim 2, characterized in that, Step (4): The alkali metal is one or more of Li, Na and K, with a content of 1-5 wt%, preferably Na and 1 wt%. Finally, calcine in a N2 atmosphere at 400-700℃ for 4-8 h, preferably 650℃ and 4 h.

7. The application of an Fe-based catalyst for CO2 hydrogenation to sustainable aviation fuel (SAF) as described in claim 1, characterized in that, FeC is obtained by in-situ carbonization of pure H2 or (CO / H2) gas at 350-400℃ and 0.1-1.0 MPa. x Active species. The preferred carbonization conditions are a pure H2 atmosphere, 400°C, and 0.1 MPa.

8. The application of an Fe-based catalyst for CO2 hydrogenation to sustainable aviation kerosene (SAF) as described in claim 1, characterized in that... The production of aviation fuel by CO2 hydrogenation is carried out in a fixed-bed reactor, characterized by a reaction temperature of 300-400℃, with an optimal temperature of 350℃. The mass hourly space velocity (WHSV) is 5000-20000 mL / g. cat The optimal space velocity is 10000 mL / g. cat The reaction pressure is 1-4 MPa, with the optimal pressure being 3 MPa.

Citation Information

Cited By

  • Bifunctional catalyst for preparing aviation fuel through COX hydrogenation as well as preparation and application of bifunctional catalyst

    CN121797391A